Anthropological inquiry into the force of the emotions in the family of man : an overview - Fernández, James W. (ENDOXA, 2014)
The argument of this essay, in its concern with human emotion, moves (an important word for its argument) in two directions and through three sequential sections. We can imagine this movement as a «zooming out» and a «zooming in» while thinking about and inspecting the emotionally entangled cultural creatures that we humans are in our social lives in culture. As appropriate to a general anthropology and as appropriate to an introductory statement we move out almost to maximal focus and consider our emotionality in terms of our neoteny, which is to say our long dependency on others as the entirely social animals that we are. Next readjusting our focus we move in upon the discipline of anthropology. We have made this movement towards, or many of us anyway have made it, importantly under the pressure of the feminist critique which, itself, has struggled to get out from under the gendering of our professional understanding by which gendering reason was assigned to masculinity and emotion to femininity. Thirdly in our sequential refocusing, and as an almost inevitable expression of our culture of individualism —we zoom in upon the career of the present author. We see him as over forty years he has moved from a formal, Cartesian— like, vectoral structuring of the emotional vicissitudes of social life, deductive in nature by attempting a deeper understanding of ethnographic responsibility to the emotions he has experienced in his various fieldwork in Africa and Europe. Finally in conclusion we zoom out again, jumping scales again, by taking up the inescapable necessity, at a time of globalization, of considering the emotions at play in national and international contexts.